P182 Prophylactic doxycycline following Indwelling Pleural Catheter insertion for malignant pleural effusions. (12th November 2015) - Nuttall, E; Balata, H; Al-Aloul, M; Evison, M; Holme, J
Abstract : Introduction: The insertion of indwelling pleural catheters (IPCs) allows outpatient based management of malignant pleural effusions. This group of patients frequently require chemotherapy and there is concern over infection rates from IPCs which has the potential to delay or prevent such treatment. The infection rate was reported as 10% in a prospective trial of IPCs. In our tertiary pleural service we have elected to routinely prescribe 7 days doxycycline 100 mg once daily following IPC insertion. This study examined our infection rates using this practice. Method: Data was collected from a tertiary respiratory and pleural service. Prospective data is collected on all patients undergoing IPC insertion at UHSM. Immediate post-procedure data is collected and a further clinical and case-note review undertaken at 6 months. Pre-defined immediate (post-procedure), early (30 days) complications are recorded. Infection is defined as the prescription of antibiotics (oral or intravenous) for suspected or confirmed pleural infection or drain-site cellulitis. This study is a retrospective review of the prospectively maintained database. To ensure six months of follow-up data for all patients the analysis was restricted to patients undergoing IPC insertion prior to 31/12/2014. Results: 62 patients with complete datasets underwent IPC insertion between 01/01/2013 and 31/12/2014. All patients received 7 days of prophylactic doxycycline at a dose of 100 mg OD. One patient (1.6%) suffered drain site cellulitis requiring antibiotics within 30 days of insertion. There were two cases (3.2%) of pleural infection treated with antibiotics (both within 30 days of insertion and required intravenous antibiotics and admission). In these cases the IPCs were not removed but it did fall out in one case where the patient developed delirium with infection. Conclusion: The infection rate in this prospectively collected data is lower than rates reported in large prospective randomised controlled clinical trials. This may suggest a benefit from the routine use of prophylactic antibiotics. A randomised controlled trial of prophylactic antibiotics versus no antibiotics following IPC insertion may be warranted.